North America : including the most recent discoveries in the Arctic Seas and West Coast, from government charts and reports, United States surveys &c. - A. Fullarton & Co. (Cartographer)
Map of North America with parts of the Caribbean, South America, Iceland, Greenland, and Asia included. Shows anglo/European names for Indigenous people, place names, contours, waterways, and references. Information from much earlier time than likely publication of map. Relief shown by hachures. Scale 1:18,057,600 Includes independent state of the Republic of Yucatán. Printed by A. & J. Macpherson, Royal Exchange, Edinbrugh. Hand coloured. Originally published in serial form beginning 1854. Subsequently published in : The Royal Illustrated Atlas, Of Modern Geography With An Introductory Notice By Dr. N. Shaw, Secretary To The Royal Geographical Society &c. A. Fullarton And Co. London And Edinburgh. Lake Nipissing looks like a grocery bag Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .